Exchange Rate and International Trade: Case From Indonesian Manufacturing Sector - Anung Yoga Anindhita (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
Exchange rate fluctuation in Floating Exchange Rate Regime is considered to Exchange rate fluctuation in Floating Exchange Rate Regime is considered to have impacts on the international trade through its adjustment to the price and its volatility to the trade risk. This paper is aimed at estimating those impacts on the international trade of manufacturing sector in Indonesia for period 2007 to 2014. To conduct estimation, it uses multiple regression analysis on two models: First, the import of raw-and-auxiliary materials; Second, the export of manufacturing sector. The results show that the exchange rate impacts both work significantly on the import of raw-and-auxiliary materials. The finding implies that, through the import of raw-and-auxiliary materials, manufacturing sector is very susceptible to the shock caused by exchange rate changes. Meanwhile, the export of manufacturing sector is not able to take advantage of the depreciation of the exchange rate due to the lack of competitiveness.DOI: 10.15408/sjie.v6i2.5210